Investigating catastrophic health expenditure among people living with HIV and AIDS in South Western Nigeria - Adeyinka Adeniran; Omobola Y. Ojo; Florence C. Chieme; Yeside Shogbamimu; Helen O. Olowofeso; Imane Sidibé; Oladipupo Fisher; Monsurat Adeleke (Wiley, 2023)
Abstract Background This study aimed to determine the catastrophic healthcare expenditure (CHE) among people living with HIV (PLHIV) in Lagos and to identify factors associated with CHE among them. Methods The study was a descriptive cross‐sectional survey conducted between January and March 2021 among 578 PLHIVs drawn from various healthcare facilities in Lagos where HIV care and treatment services should be provided free of charge. Data were collected through pretested questionnaires and analyzed using Stata SE 12. Results The mean monthly expenditure on food was N29,282 ($53.2), while expenditure on healthcare averaged N8364 ($15.2). Nearly 60% of respondents experienced CHE, while around 30% had to borrow money to pay for some aspect of their medical treatment. Almost all (96%) had no health insurance plan. Respondents' group, personal income, perception of current health status, and the number of people in their households were significantly associated with catastrophic health expenditure p < 0.05. PLHIV in the racial/ethnic minority/migrants' group and those who earned less than ₦30,000 ($55) were statistically significantly associated with CHE at p < 0.001 with OR of 28.7 and 3.15, respectively. Conclusions The study, therefore, highlights the widespread financial hardship faced by PLHIV in accessing healthcare, and the need for policies to increase financial risk protection.